Triggered Recurrence Factors of Mental Illness Patients in an Emergency Unit in a Psychiatric Hospital - Selvya Hesti Andriyani; Ana Oktarisa; Arum Pratiwi (Jurnal Ners, 2019)
Introduction: Understanding the trigger recurrence factors of mental illness patients is important because the number of mental hospital visits has been increasing every year, especially in mental illness patients who have experienced recurrence. This research aimed to identify and describe some of the types of trigger that result in recurrent readmission to the emergency unit of a psychiatric hospital.Methods: The study was designed using a quantitative method with a univariate and bivariate analysis approach using a cross-sectional design. The researcher conducted the study in the Emergency ward of Surakarta mental hospital for 2 months and obtained 71 total samples on patient readmission where there was a recurrent mental illness. The samples were taken using the accidental sampling technique. The data was taken using a questionnaire and analyzed using narrative description and central tendencies.Results: The results showed that the highest trigger recurrence factors were 58% related to patient compliance when taking medication. The results showed that there are various triggers for the recurrence of mental illness.Conclusion: These were evidenced by the family members who stated that they found the medication around the house or in the patient’s shirt pocket. The other trigger recurrence factors which were categorized as less influential were family support and the environment of society, which were 4%.